Risk Management: Challenges For Village Government in Managing Village Funds, in Indonesia - Arwanto Harimas Ginting; Yetty Sembiring (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2025)
This study reviews the challenges in implementing risk management for village fund management and provides insights based on current practices. Risk management provides a process for addressing risks associated with managing village funds; however, it faces barriers, particularly at the village level within government organizations. The work background and educational experience of village heads and officials are key obstacles in applying the RM village fund management. The study uses a qualitative, descriptive approach; locations were selected based on established criteria for independent villages in mountainous areas. Data collection involved interviews, searching documents for regulations, followed by analysis through preparation, reading, viewing, coding and interpretation. This study identified eight types of risk, categorized into two groups, during the implementation of risk management for the misuse of village funds. Therefore, providing socialization to village governments on training, policy setting, and local government support is crucial to solve challenges in village funds management. The research is limited to two villages in the mountainous region. The findings are useful for developing government science, particularly in local government management, and are necessary to achieve effective small-scale governance and development. Challenges come from both internal and external sources within the village government during risk management implementation.